PEDAGOGICAL-PSYCHOLOGICAL BASIS OF FORMING MORAL IMMUNITY AGAINST INFORMATION ATTACKS IN STUDENTS IN COLLABORATION WITH HIGHER EDUCATIONAL INSTITUTIONS AND FAMILIES (Universal International Scientific Journal, 2026)
This article analyzes the pedagogical and psychological foundations of the formation of moral immunity in students against information attacks in cooperation with higher educational institutions and families. Threats emerging in the information space, factors that negatively affect the minds of young people, and mechanisms for cooperation between family upbringing and educational institutions in eliminating them are highlighted. As a result of the research, an effective model for the development of moral immunity is proposed.
Keywords: information attacks, moral immunity, spiritual protection, family psychology, media literacy, critical thinking, social awareness, information security, digital space, globalization, communicative competence, gender stereotypes.